Digital Transformation of School Administration through Human Resource Information System Implementation - Masyhuri Masyhuri; Maysas Yafi Urrochman (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service program aims to improve administrative management effectiveness through the implementation of a web-based information system at SMK Al-Maliki Sukodono Lumajang. The main problem faced by the schools was the use of manual recording systems, which resulted in low efficiency, high risk of data errors, and limited access to information. The methods employed included needs analysis, system design, implementation, as well as user assistance and evaluation. The results indicate that the developed system successfully improved work efficiency, data organization, and reporting processes. User evaluation revealed a very high level of satisfaction, with 73% of respondents being very satisfied with the system’s benefits, 67% with access speed, and 60% with ease of use. In addition, the system encouraged a shift toward technology- and data-driven work practices. Therefore, the implementation of the web-based information system is proven effective in enhancing school administrative governance and has strong potential to be replicated in other educational institutions with similar characteristics.